Prevalence and risk factors for HPV infection in normal oral mucosa of Chilean dentistry students. - Rocío Aguirre; Ana Tapia; Alejandra Fernández; Mauricio Bittner; Alfredo Esguep (Universidad de Concepción., 2015)
Aim: To determine the prevalence and risk factors for HPV infection in normal oral mucosa of Chilean dentistry students. Materials and methods: A cross-sectional study was performed. The study group was comprised of 103 individuals between 18 and 33 years old. A self-administered survey of cancer family history, sexual habits, smoking and alcohol drinking was applied. Oral mucosal samples were taken using a sterile swab. Subsequently, all samples were analyzed by polymerase chain reaction technique (PCR). Results: Results were negative for HPV detection in all analyses. Of the study population, 58% had a family history of cancer, 40.9% had had more than 3 sexual partners, 76.3% had sexual intercourse before the age of 19, 66.3% had engaged in oral sex, 69.9% drank alcohol and 20.6% were smokers. Conclusions: The group studied is exposed to various risk factors for HPV infection, so it is necessary to educate about the relationship between them and the spread of the virus. Despite the presence of risk factors, the detected prevalence of HPV was 0%.